OPTIMUM DESIGN AND RAPID PROTOTYPING OF MECHANICSM BASED ON CAD/CAE SYSTEM AND FUSED DEPOSITION MODELING 3D PRINTING TECHNOLOGY - Thanh-Hung Ly; Thi-Than Chau; H Tho Nguyen; Thanh-Long Le; Vu-Anh-Duy Nguyen (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
Materials’ optimization for the product structure makes its weight smaller and easy to transport after manufacturing but still ensure the criteria of its strength, hardness, and capacity of good operation. These properties are extermely important and criteria need to be obtained in many field of aerospace, automotive, ship and other industries, etc. Besides, the optimization of product mass will save the materials and bring significant benefits for manufacturers and improve the environment. Thus, this paper presents the design and optimization based on the topology principles for machine mechanism and its rapid prototyping using CAD/CAE and FDM (Fused Deposition Modeling) 3D printing technology/additive manufacturing (AM). The machine elements or links are manufactured by PLA material on 3D Delta printer. The results showed that designed machine mechanism have the optimized geometry, reduced materials and satisfied the operation capacity.